CALCULATED PHASE RELATIONS IN THE SYSTEM NA2O-CAO-K2O-FEO-MGO-AL2O3-SIO2-H2O WITH APPLICATIONS TO UHP ECLOGITES AND WHITESCHISTS - Yang J.Ju.; Powell R. (My University, 2006)
Pressure–temperature grids in the system Na2O–CaO–K2O–FeO–MgO– Al2O3–SiO2–H2O and its subsystems have been calculated in the range 15–45?kbar and 550–900°C, using an internally consistent thermodynamic dataset and new thermodynamic models for amphibole, white mica, and clinopyroxene, with the software THERMOCALC. Minerals considered for the grids include garnet, omphacite, diopside, jadeite, hornblende, actinolite, glaucophane, zoisite, lawsonite, kyanite, coesite, quartz, talc, muscovite, paragonite, biotite, chlorite, and plagioclase. Compatibility diagrams are used to illustrate the phase relationships in the grids. Coesite-bearing eclogites and a whiteschist from China are used to demonstrate the ability of pseudosections to model phase relationships in natural ultrahigh-pressure metamorphic rocks. Under water-saturated conditions, chlorite-bearing assemblages in Mg- and Al-rich eclogites are stable at lower temperatures than in Fe-rich eclogites. The relative temperature stability of the three amphiboles is hornblende > actinolite > glaucophane (amphibole names used sensu lato). Talc-bearing assemblages are stable only at low temperature and high pressure in Mg- and Al-rich eclogites. For most eclogite compositions, talc coexists with lawsonite, but not zoisite, in the stability field of coesite. Water content contouring of pressure–temperature pseudosections, along with appropriate geotherms, provides new constraints concerning dehydration of such rocks in subducting slabs. Chlorite and lawsonite are two important H2O-carriers in subducting slabs. Depending on bulk composition and pressure–temperature path, amphibole may or may not be a major H2O-carrier to depth. In most cases, dehydration to make ultrahigh-pressure eclogites takes place gradually, with H2O content controlled by divariant or higher variance assemblages. Therefore, fluid fluxes in subduction zones are likely to be continuous, with the rate of dehydration changing with changing pressure and temperature. Further, eclogites of different bulk compositions dehydrate differently. Dehydration of Fe-rich eclogite is nearly complete at relatively shallow depth, whereas Mg- and Al-rich eclogites dehydrate continuously down to greater depth.
Keywords: dehydration; eclogites; phase relations; THERMOCALC; UHP metamorphism; whiteschists